ORAL NARRATIVE AND DESCRIPTIVE PROFICIENCY IN BILINGUAL CHILDREN: A CASE STUDY OF JAVANESE-INDONESIAN CHILDREN - Katharina Endriati Sukamto; Bambang Kaswanti Purwo (Masyarakat Linguistik Indonesia, 2016)
This qualitative preliminary study focuses on the linguistic proficiency of Javanese-Indonesian bilingual elementary school children in a village in Gunung Kidul, 65 km south of Yogyakarta in the island of Java, Indonesia, in producing oral narrative and descriptive stories in Javanese and Indonesian. Two kinds of instruments were used to elicit data in this study: a six-minute silent movie and a picture about some activities to commemorate the Indonesian Independence Day. The elicited data from the movie instrument shows that both the lower-grade and higher-grade students were more at ease with Javanese than with Indonesian. From the picture-triggered speech, the result is that the higher-grade students superseded the lower-grade students in their fluency in Indonesian as well as in their ability to construct longer utterances in the language. This study demonstrates that the children’s proficiency in Javanese – their first language – remains at the basic level and it does not develop even though the children are in the higher grade. However, all children are more comfortable with Javanese when they have to do retelling. When the children were given a task that is related to academic requirements, such as describing something that is based on a picture, the higher-grade children perform better in Indonesian rather than in Javanese.